Experiment and Analysis of Gearbox Shell Vibration Modal based on DASP - Ma Weijin; Zhang Lin; Zhang Jiping; Huang Bincheng; Ge Yumin (Jixie chuandong)
Through the experiment of the vibration modal of gearbox shell,the gearbox shell vibration state is analyzed and the stability of its operation is evaluated.By using DASP（Data Acquisition& Signal Processing）software,the vibration modal of the HW25505 TCL type aluminum alloy gearbox shell is tested.By the contrast between ERA method and PloyLSCF method,the reliable 14order of frequency and damping are obtained,and thus the vibration mode analysis is carried out.By using modal correlation matrix of modal to test and verify,through the comparison with calculating modal,the validity and reliability are proved.Applied DASP to vibration modal test of gearbox shell,not only the gearbox shell high order frequency,damping,vibration mode,and vibration condition can be acquired,but also the vibration problem of similar shell gearbox in operation can be solved,The theoritical basis for the improvement of the gearbox shell structure characteristics and the fault diagnosis of gearbox shell are provided,and had better promotion value in engineering practice.